A novel topology of modular multilevel bidirectional non-isolated dc-dc converter - Monteiro, Vítor Duarte Fernandes (2020)
The paradigm of smart grids has been continuously addressing new challenges in terms of power electronics converters, for instance, to deal with technologies like renewables, electric mobility, energy storage, and hybrid power grids. Allied with this context, a novel topology of modular multilevel bidirectional (MMB) non-isolated dc-dc converter is proposed in this paper. Taking into consideration the nature of the proposed MMB dc-dc converter, it is appropriated to operate as back-end converter linked to front-end ac-dc converters based on cascade structures, i.e., with more than one dc-link. As distinctive features, the proposed MMB dc-dc converter can operate with five-voltage levels, allowing to reduce the voltage stress in each semiconductor, and it is controlled based on the interleaved principle of operation, although it is not an interleaved converter. A dedicated pulse-width modulation, as well as voltage and current control strategies, are proposed and clearly explained along the paper. The claimed distinctive features of the proposed MMB dc-dc converter are supported by analytic description and by computer simulation validation, considering steady-state and transient-state operations in relevant conditions of the dc interfaces.